Determinants of Pentagon Fraud in Detecting Financial Statement Fraud and Company Value - Heru Satria Rukmana (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Purpose of this study was to analyze the determinants of fraud pentagon, namely pressure, opportunity, rationality, capability and arrogance of fraudulent financial statements and value. company. The research sample was 66 manufacturing industrial companies indicated to report financial fraud. Methods of data analysis using regression with panel data. The results showed: Positive pressure on fraudulent financial statements, the more widely used to obtain finance, making outsiders, insiders and financial targets, the greater the fraudulent financial statements; Positive opportunities for financial statement fraud. This shows that there is no factor in the false financial statements; Positive arrogance against fraudulent financial statements. This shows that as arrogance increases, fraudulent financial reports will increase.The deviation from negative financial statements to financial reports, the greater the company's profits and profits will increase in the long run; Positive pressure on firm value, the more opportunities to get gross profit margin, net cash flow, total managerial ownership, return on assets, firm value will increase; Negative company opportunities for firm value. It shows that nothing bigger and ineffective will improve company performance; Positive rationalization of fraudulent financial statements, so that the greater the ratio to get the amount of accruals to total assets, the greater the firm value; The ability to have a positive relationship with company value. This shows that the determining factor or controlling the running of the company so that the value of the company will increase; Positive attitude towards company value. This shows that increasing arrogance will increase the value of the firm; positive pressure on financial reports, greater amounts of financial information to obtain, costs from outside parties, other parties within and financial targets so that fraudulent financial statements will be greater to increase company value; Positive opportunities for financial reports. This shows that nothing is greater than the job and the ineffectiveness of a good commissioner and fraudulent financial reports will be increasingly bigger to increase the value of the company; A positive rationalization of firm value through fraud in financial statements, so that the greater the total accruals to total assets, the greater the fraudulent financial statements will increase firm value; Financial reporting capabilities. This shows that the greater the value of ownership increases through waning financial statements; Pride against corporate value from fraudulent financial statements. This shows that the more money will increase.Â